2014
DOI: 10.1016/j.neubiorev.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling in neuropsychiatric disorders: Ties with adult hippocampal neurogenesis and behavior

Abstract: In an effort to better understand and treat mental disorders, the Wnt pathway and adult hippocampal neurogenesis have received increased attention in recent years. One is a signaling pathway regulating key aspects of embryonic patterning, cell specification, and adult tissue homeostasis. The other is the generation of newborn neurons in adulthood that integrate into the neural circuit and function in learning and memory, and mood behavior. In this review, we discuss the growing relationship between Wnt signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 177 publications
2
53
0
Order By: Relevance
“…A tight link between hippocampal plasticity, depression, and memory has been suggested [141], and antidepressants were found to modulate hippocampal LTP [142,143]. Wnt signaling components are expressed in the adult dentate gyrus, and the regulation of Wnt expression is accompanied with evidence of change in neurogenesis, suggesting that Wnt signaling is a principal regulator of adult hippocampal neurogenesis [136]. Microarray analysis demonstrated that citalopram, fluoxetine, venlafaxine, and atomoxetine modulate rat hippocampal gene expression of Wnt pathway components [144].…”
Section: Neuronal Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…A tight link between hippocampal plasticity, depression, and memory has been suggested [141], and antidepressants were found to modulate hippocampal LTP [142,143]. Wnt signaling components are expressed in the adult dentate gyrus, and the regulation of Wnt expression is accompanied with evidence of change in neurogenesis, suggesting that Wnt signaling is a principal regulator of adult hippocampal neurogenesis [136]. Microarray analysis demonstrated that citalopram, fluoxetine, venlafaxine, and atomoxetine modulate rat hippocampal gene expression of Wnt pathway components [144].…”
Section: Neuronal Plasticitymentioning
confidence: 99%
“…Recent studies have largely focused on identifying cellular and molecular mechanisms underlying hippocampal plasticity in response to stress and antidepressant treatments. Changes in neurotrophin level and activity (e.g., activin pathway [134], BDNF, and CREB1 [135]), intracellular signaling pathways (e.g., Wnt signaling [136] and mTOR signaling [137]), direct modulators of synaptic plasticity (e.g., GAP43 [138]), and/or synaptic function/structure (SNAP25, DLG2, MAP1A) and glutamate receptor subunits (GLUR1 and GLUR3) [139] have been implicated. Pathway analyses in depressive subjects have been scarcely performed, and these data mainly derived from analyses on single molecules pertaining to a pathway and/or animal models.…”
Section: Neuronal Plasticitymentioning
confidence: 99%
“…While this is the case in mature, differentiated cells under basal conditions, the activity of GSK3 is much lower in stem/precursor cells due to the action of growth factors and Wnt molecules. Therefore, in BD over activity of GSK3 may undermine neurogenesis, and psychotropic agents by enhancing this process promote mood stabilization 27). Further, detailed characterization of this mode of action of mood stabilizing medications can result in targeted therapeutics of BD.…”
Section: Main Subjectsmentioning
confidence: 99%
“…The wnt/β-catenin signal pathway has emerged as a crucial pathway in neuronal self-renewal, proliferation, differentiation, maturation, and functional integration [10]. It has been proved to facilitate long-term potentiation [11] and deregulation of the wnt/β-catenin pathway has been implicated in the pathology of AD [12].…”
Section: Introductionmentioning
confidence: 99%